INOVASI MODEL PEMBELAJARAN PANTUN: UPAYA MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS, KERJASAMA DAN TANGGUNG JAWAB SISWA SEKOLAH DASAR - Muhammad Hidayat; Akhmad Riandy Agusta (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The background of this study is the low level of student engagement in the learning process and the underdevelopment of critical thinking skills, cooperation abilities, and sense of responsibility. These issues are caused by a lack of variety in learning models, a predominantly one-way learning process, and minimal active student involvement. To address these problems, a combination of Problem Based Learning (PBL), Numbered Heads Together (NHT), and Teams Games Tournament (TGT) learning models was implemented. The purpose of this study is to describe and analyze the teacher’s actions during instruction, as well as to evaluate improvements in student activity, critical thinking skills, cooperation, responsibility, and learning outcomes. This study employed a Classroom Action Research (CAR) approach conducted with third-grade students of SDN Telawang 4 Banjarmasin over three sessions. The findings indicate an increase in teacher activity from the “good” to “very good” category. Meanwhile, student activity significantly improved from “less active” to “very active.” Students’ critical thinking skills showed remarkable development, shifting from predominantly less critical to more actively critical thinkers. This improvement positively impacted student learning outcomes across affective, cognitive, and psychomotor domains. Overall, the results demonstrate that the combined application of PBL, NHT, and TGT models effectively enhances the quality of learning comprehensively.